Giving children a better start: Pre-school attendance and school-age profiles - Samuel Berlinski; Sebastian Galiani; Marco Manacorda (Institute for Fiscal Studies (IFS), 2006)
We study the effect of pre-primary education on children's subsequent school outcomes by exploiting a unique feature of the Uruguayan household survey (ECH) that collects retrospective information on preschool attendance in the context of a rapid expansion in the supply of preprimary places. Using a within household estimator, we find small gains from preschool attendance at early ages that magnify as children grow up. By age 15, treated children have accumulated 0.8 extra years of education and are 27 percentage points more likely to be in school compared to their untreated siblings. Instrumental variables estimates that control for non random selection of siblings into pre-school lead to similar results. We speculate that early grade repetition harms subsequent school progression and that pre-primary education appears as a successful policy option to prevent early grade failure and its long lasting consequences. – Preschool ; Pre-primary education ; Primary school performance
Keywords: I2; J1; 330; Allgemeinbildende Schule; Kinderbetreuung; Uruguay